2020
DOI: 10.1177/0022034520906138
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome and Gingival Transcriptome Profiles of Ligature-Induced Periodontitis

Abstract: This investigation evaluated the relationship of the oral microbiome and gingival transcriptome in health and periodontitis in nonhuman primates ( Macaca mulatta). Subgingival plaque samples and gingival biopsies were collected from healthy sites and at sites undergoing ligature-induced periodontitis. Microbial samples were analyzed with 16S amplicon sequencing to identify bacterial profiles in young (3 to 7 y) and adult (12 to 23 y) animals. The gingival transcriptome was determined with a microarray analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…Beyond the clear differences in the host gingival response, changes in the oral microbiome also occur during ligatureinduced periodontitis, in many ways similar to the differences that have been reported with human disease (43,53). This study identified unique features of the microbiome in disease that significantly correlated with these changes in the gingival transcriptome.…”
Section: Discussionsupporting
confidence: 66%
“…Beyond the clear differences in the host gingival response, changes in the oral microbiome also occur during ligatureinduced periodontitis, in many ways similar to the differences that have been reported with human disease (43,53). This study identified unique features of the microbiome in disease that significantly correlated with these changes in the gingival transcriptome.…”
Section: Discussionsupporting
confidence: 66%
“…Different proteome and microbiome studies have been performed to understand periodontal diseases, yet few have focused on gingival tissues. Earlier studies indicated that the microbial content of the periodontal pocket in non-human primates or human determines the gene expression patterns in the gingival tissues (Papapanou et al, 2009 ; Ebersole et al, 2020 ). In the present study, we successfully applied a contemporary PCT-assisted workflow to dissect the gingival proteome and microbiome of both diseased and healthy sites from patients with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ligatures in primates do elicit both soft and hard tissue changes related to periodontal lesions, albeit, generally the animals do not lose substantial bone architecture in this experimental model that does occur in naturally occurring disease. Second, while the ligature clearly increases the accumulation of bacteria and does provide some mechanical disruption to the tissues that differs somewhat from human disease, the oral microbiome in the nonhuman primates shows extensive overlap in changes observed with naturally occurring 57 and ligature‐induced disease 56,109 . Additionally, we have shown that gingival gene expression profiles documenting local host response features for a number of pathways are comparable in naturally occurring and ligature‐induced disease models 47,110 .…”
Section: Discussionmentioning
confidence: 74%
“…Finally, epidemiologic data support various demographic modifiers (e.g., age, sex) of periodontitis expression in humans, as well as the identification of substantial individual variation in risk for more extensive and severe disease. While the ligature model does not necessarily reflect this individual feature of human periodontitis, we have shown that the magnitude of ligature‐induced disease in the nonhuman primates is altered by age 56 and sex, 111 as well as recent data demonstrating matriline (e.g., genetic, familial) susceptibility age of onset and extent of disease 112,113 . Thus, the evidence suggests that this model should be able to provide some insights into the earliest phases of disease initiation and progression that would be difficult to obtain in a human disease model.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation